2018
DOI: 10.1016/j.tjem.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Whole body computed tomography in multi trauma patients: Review of the current literature

Abstract: Many authors adopt the Selected Computed Tomography (SCT) approach of the Advanced Trauma Life Support (ATLS) for the management of multiple trauma patients. In the SCT approach, the initial physical examination is followed by conventional radiography (cervical X-ray, chest X-ray, pelvic X-ray and Focused Abdominal Sonography in Trauma (FAST)), and the computed tomography (CT) of the specific body regions if indicated. An alternative to this traditional approach is the Whole-body Computed Tomography (WBCT) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 39 publications
1
32
1
7
Order By: Relevance
“…Some special rules of clinical research should be applied for specifying the requirement for imaging of the c spine in trauma patients who are hemodynamically stable. [32]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some special rules of clinical research should be applied for specifying the requirement for imaging of the c spine in trauma patients who are hemodynamically stable. [32]…”
Section: Methodsmentioning
confidence: 99%
“…Correspondingly, CT imaging is an essential part of the current medical diagnosis procedure [Figure 3]. [32] Huber et al . [33] have shown that full-body CT scan could easily enhance the survival rate of patients who have blunt trauma.…”
Section: Methodsmentioning
confidence: 99%
“…Компьютерная томография (КТ) обладает оптимальными характеристиками для диагностики травм из-за возможности достаточно быстрого обследования при высокой чувствительности и специфичности [12]. КТ всего тела в настоящее время является ключевым методом для первоначальной оценки состояния пациентов с политравмой в основных травмцентрах [13]. Большие исследования показали, что КТ всего тела значительно снижает смертность у пострадавших с политравмой и ассоциируется с лучшими результатами, чем целевая КТ [14].…”
Section: Introductionunclassified
“…Whole-body computed tomography (WBCT) makes this possible [4]. WBCT is recommended as a standard and basic diagnostic method for trauma patients [5,6]. The standard protocol of the WBCT is divided in two stages.…”
Section: Introductionmentioning
confidence: 99%